Experimental Investigation on Friction Drilling of Stainless Steel AISI 304 - Dehghan, Shayan; Ismail, Mohd Idris Shah; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B.T. Hang Tuah; Parnianifard, Amir (Inderscience Publishers, 2019)
Friction drilling is an unexplored manufacturing process to produce holes in thin-walled sheet metals. In this study, the effects of process parameters in friction drilling of austenite stainless steel investigated experimentally and statistically. It was confirmed, sufficient heat generation, which cause to better bushing shape and height, acceptable drilled-hole diameter and lowest roundness error result from low spindle speed and high feed rate. It was obtained, although effect of feed rate on hole-wall thickness was negligible; spindle speed has significant effect on that which is inverse from spindle speed effect on bushing height. Moreover, micro-hardness reduced gradually away from the drilled-hole edge. Observing on tool shape and wear damage using optical microscope and scanning electron microscope quantifies effects of spindle speed and feed rate on tool performance and tool wear characteristics. Results indicate that better performance of drilling tool obtained from lower spindle speed and high feed rate.